2013
DOI: 10.1002/grl.50762
|View full text |Cite
|
Sign up to set email alerts
|

The cooling‐rate effect on microwave archeointensity estimates

Abstract: [1] New microwave (MW) paleointensity data on historical bricks from Northeast Brazil presented a bias toward higher fields when compared to previous cooling-rate corrected double-heating paleointensity estimates; the same relates to the previously reported values for pottery from Southwestern Pacific islands. A simple theoretical approach suggests that the MW bias in both collections is due to a cooling-rate effect on MW estimates. We then experimentally corrected the MW cooling-rate effect on Brazilian fragm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 38 publications
0
12
0
Order By: Relevance
“…However, some conversion to thermal energy to heat the matrix is likely and pTRM-checks test are now integrated in the microwave technique. Recent studies have also included checks for evaluating the cooling rate effect (e.g., Poletti et al, 2013;Ertepinar et al, 2020).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…However, some conversion to thermal energy to heat the matrix is likely and pTRM-checks test are now integrated in the microwave technique. Recent studies have also included checks for evaluating the cooling rate effect (e.g., Poletti et al, 2013;Ertepinar et al, 2020).…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Since the MW‐Perp and the Th‐Perp data sets are not statistically distinguishable, any cooling rate effect would be relatively minimal. Further, the MW‐OT data have a faster cooling rate but give lower estimates than the Th‐OT data, which is the opposite of the expected cooling rate effect (Poletti et al, 2013).…”
Section: Discussionmentioning
confidence: 88%
“…As in this case the field was applied in the direction of NRM, no anisotropy correction had to be performed. The higher mean result obtained might be ascribed to the fast cooling rate of this method (Poletti et al, 2013). One sample did not provide reliable results due to alteration during the microwave experiment.…”
Section: Fraction and Domain-state Corrected Multispecimen Methods (Msmentioning
confidence: 87%
“…In the microwave determinations the field is applied in the same direction as the natural remanence, thus no anisotropy correction has to be applied in this case. Poletti et al (2013) demonstrated that for a set of Brazilian ceramics the differences in cooling rate between the MW and standard heating methods can result in overestimates of MW results of up to 25%. The higher average results obtained from the MW may be due to cooling rate.…”
Section: Microwave Methods (Mw)mentioning
confidence: 99%